KOMUNIKASI DALAM ADAPTASI BUDAYA (Studi Deskriptif pada Mahasiswa Fakultas Ilmu Sosial dan Humaniora UIN Sunan Kalijaga Yogyakarta) - Fajar Iqbal (Profetik: Jurnal Komunikasi, 2014)
Students of the Faculty of Social Sciences and Humanities, UIN Sunan Kalijaga Yogyakarta has a wide range of cultural backgrounds. Not only geographically, but also culturally different based on their family backgrounds and socio economic strata. This article tries to describe the communication students of the Faculty of Social Sciences and Humanities in adapting to the UIN Sunan Kalijaga environment. Based on the analysis of in-depth interviews have been conducted, researchers found that the informants did venture proactive information retrieval in order to adapt to the environment where he or she was educated at UIN Sunan Kalijaga. However, major subjects are individuals with personal identity and distinctive characteristics that communicate and interact socially, they do not lose their identity and uniqueness.